2021
DOI: 10.1111/cns.13629
|View full text |Cite
|
Sign up to set email alerts
|

A potential association of RNF219AS1 with ADHD: Evidence from categorical analysis of clinical phenotypes and from quantitative exploration of executive function and white matter microstructure endophenotypes

Abstract: Aims Attention‐deficit/hyperactivity disorder (ADHD) is a neuropsychiatric disorder of substantial heritability, yet emerging evidence suggests that key risk variants might reside in the noncoding regions of the genome. Our study explored the association of lncRNAs (long noncoding RNAs) with ADHD as represented at three different phenotypic levels guided by the Research Domain Criteria (RDoC) framework: (i) ADHD caseness and symptom dimension, (ii) executive functions as functional endophenotype, and (iii) pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Importantly, circGNB1 overexpression increased OA severity in the DMM mouse model, whereas circGNB1 silencing had the opposite effect. RNF219 (also known as C13orf7) plays a role in prostate tumors, 47 attention-deficit/hyperactivity disorder 48 and other diseases, 49 although its role in OA remains unclear. In this article, our results indicated that RNF219 expression was up-regulated in the cartilage of the medial tibial plateaus in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, circGNB1 overexpression increased OA severity in the DMM mouse model, whereas circGNB1 silencing had the opposite effect. RNF219 (also known as C13orf7) plays a role in prostate tumors, 47 attention-deficit/hyperactivity disorder 48 and other diseases, 49 although its role in OA remains unclear. In this article, our results indicated that RNF219 expression was up-regulated in the cartilage of the medial tibial plateaus in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the potential roles of lncRNA in the genetic etiology of ADHD have shown the relationship of the SNP in BC200RNA, RNF219-AS1, STXBP5-AS1 with ADHD. (Arias-Vásquez et al, 2019; Fu, Chen et al, 2021; Kahaei et al, 2020).…”
Section: Introductionmentioning
confidence: 99%